LEGAL PROTECTION FOR CHILD VICTIMS OF SEXUAL ABUSE (A STUDY AT MADINA POLICE DEPARTMENT) - Arie Sofandi Palih; Rizkan Zulyadi; Serimin Pinem (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This research examines legal protection for child victims of sexual abuse in the jurisdiction of the Mandailing Natal Police Department (Polres Mandailing Natal). The main focus of the research is to explore how legal procedures are implemented by the police in handling cases of child sexual abuse and to what extent legal protection is provided to the victims from juridical, social, and psychological perspectives. This research uses a qualitative method with a descriptive case study approach. Data collection techniques include in-depth interviews, direct observation, and document study. The informants in this research consist of officers from the Women and Children Protection Unit (UPPA), legal advocates, and psychologists. The findings indicate that legal protection for child victims of sexual abuse at Polres Madina is based on applicable legal provisions, including the Child Protection Law and the Criminal Code, and is complemented by child-friendly procedures during the investigation process. However, the implementation still faces several challenges, such as limited human resources, suboptimal inter-agency coordination, and low public legal awareness. Other obstacles include socio-cultural factors that often hinder the reporting process and protection of victims. The conclusion of this study states that although legal protection for child victims of sexual abuse at Polres Madina has been procedurally implemented, its effectiveness still needs improvement. The study recommends enhancing the capacity of law enforcement officers, providing integrated services for victims, and strengthening legal education for the public to create a more responsive and just child protection system.